Аналіз впливу комбінації стрес-корозійних чинників на корозійне розтріскування від напруження трубної сталі при рН, близьких до нейтральних - Ниркова, Людмила Іванівна (НТУ "ХПІ", 2017)
Досліджено корозійно-механічні властивості трубної сталі типу Х70 в умовах комбінації чинників, за яких можливо корозійне розтріскування від напруження (КРН) Встановлено, що при потенціалі корозії, накопичених напруженнях у присутності локального осередку корозії (ЛОК) трубна сталь проявляє схильність до КРН за змінного змочування, яке не проявляється при повному зануренні. Змінне змочування за потенціалу -1,0 В в деякому ступені може прискорювати процес КРН. Схильність до КРН сталі з накопиченим рівнем напружень та ЛОК однакова як при повному, так і при змінному змочуванні, що вказує на превалюючий вплив на процес КРН катодного потенціалу та ЛОК порівняно із змінним змочуванням.

Corrosion-mechanical properties of pipe steel Х70 in model soil electrolyte (MSE) under influence of different combination of factors were investigated. It was established that factors which led to stress-corrosion cracking (SCC), are corrosion environment, applied loads (stretching and cyclic) and cathodic potential. The presence of local corrosion defect (LCD) and variable moistening may promote in some extent SCC process. For example, under variable moistening by MSE at corrosion potential the pipe steel specimens with accumulated cyclic stress and LCD demonstrate the inclination to SCC, which don’t not occur at full immersion. At applied cathodic potential -1,0 V both at full immersion and at variable moistening pipe steel specimens in the initial state, with accumulated cycle stress without LCD and with accumulated cycle stress and LCD show the inclination to SCC. It should be noted that inclination to SCC of pipe steel with accumulated cyclic stress and in the presence of LCD is practically identical both at full immersion and at variable moistening, that indicate on prevail influence of cathode potential and LCD over variable moistening.
Analysis of influence of stress-corrosion factors combination on stress-corrosion cracking of pipe steel at near neutral рН
Keywords: магістральний газопровід; МГ; циклювання; КРН; корозійно-механічні властивості; локальний осередок корозії; ЛОК